EXPERIENCIA PERCEPTIVA Y FALSOS PLANOS SUBJETIVOS EN EL ECLIPSE (MICHELANGELO ANTONIONI, 1962) Y MUERTE EN VENECIA (LUCHINO VISCONTI, 1971) - Dr. Víctor AERTSEN (Fonseca, Journal of Communication, 2023)
Point-of-view shots are a powerful resource when they are used in their canonical structure, but they also have great aesthetic potential when this structure is altered to break the spectator’s expectations. For example, in the cases of «false point-of-view shots» in which the viewer faces the need to reassess the subjective condition of the plane that she observes when the character with whom he thought she was sharing the look appeares in it. All false point-of-view shots produce experiences that share certain phenomenological qualities caused by the way they act on the expectations and perception of the viewer